EU Enlargement and Geopolitics: Is it Relevant Today? - Domaradzki, Spasimir (Identities: Journal for Politics, Gender and Culture, 2023)
After the Russian full-scale invasion in Ukraine geopolitics has entered anew the European integration vocabulary. The EU official rhetoric consistently reiterates geopolitics as a driving factor for its renewed enlargement mobilization. The swift appearance of the enlargement perspective for Ukraine and Moldova as well as the pursiut of geopolitical momentum for the approximation with the Western Balkans countries provoked diverse reactions from enthusiasm to questions about the practical consequences for the EU, its enlargement policy and the particular member states. This article raises the argument that the EU’s geopolitical rhetoric plays much more important role in the search for an exit from the EU’s internal political deadlock, than as a genuinely new geopolitical boost that will revive or speed up the enlargement process. The geopolitical argument aims to instrumentalize the enlargement policy in search of a new step towards the deepening of the European integration, making enlargement a hostage to EU’s internal problems. Author(s): Spasimir Domaradzki Title (English): EU Enlargement and Geopolitics: Is it Relevant Today? Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 20, No. 1-2 (2023). Publisher: Institute of Social Sciences and Humanities - Skopje Page Range: 20-31 Page Count: 12 Citation (English): Spasimir Domaradzki, "EU Enlargement and Geopolitics: Is it Relevant Today?,” Identities: Journal for Politics, Gender and Culture, Vol. 20, No. 1-2 (2023): 20-31.